On the Power and Limits of Empathy - Camassa, Manuel; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This book has two main objectives. The first is to identify and adequately describe the phenomenon of empathy. This essentially means offering a strong, reasoned and accurate description of the phenomenon of empathy in order to capture the essence of the empathic phenomenon and clearly distinguish it from other similar emotional phenomena such as sympathy or compassion The second part focuses on the role that this phenomenon can play on the ethical-moral level. The question is whether empathy is necessary or at least important for morality, and if so, to what extent, in what way and for what reasons. This is an open access book.
Part 1: What is Empathy? -- 1: A Brief Historical Reconstruction -- 2: The Way to a Definition -- 3: A Taxonomy of Empathy -- 4: Conclusions to Part 1 -- Part 2: Empathy and Morality -- 5: Anti-Empathism -- 6: The Bright Side of Empathy -- 7: Conclusions.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Ethics; Philosophy of mind; Moral development; Moral Philosophy and Applied Ethics; Moral Psychology; Moral Development